DIGITAL ECONOMY: CONCEPT AND DEVELOPMENT TRENDS - Kamalova Jamila (American Journals, 2023)
The Digital Economy is an economic activity focused on digital and electronic technologies. This includes e-business and commerce, as well as the goods and services they produce. Essentially, this definition covers all business, cultural, economic and social transactions carried out on the Internet and through digital communication technologies. The following article is devoted to the study of digital economy and its development trends.
Keywords: Digital economy, cloud technology, bitcoin, cryptocurrency, e-commerce, internet of things, web money, Qiwi wallet.